2001
DOI: 10.1038/sj.ejhg.5200716
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of trinucleotide repeats in loci DM, DRPLA and SCA1 in East European populations

Abstract: A normal polymorphism at three triplet repeat loci (myotonic dystrophy (DM), dentatorubral-pallidoluysian atrophy (DRPLA) and spinocerebellar ataxia type 1 (SCA1)) were examined in healthy unrelated individuals from the Siberian Yakut (Mongoloid) population, the Adygei (Caucasian) population and nine East European populations: populations from Russia (Holmogory, Oshevensk, Kursk, Novgorod, Udmurts, Bashkir), two Ukrainian populations (Lviv and Alchevsk) and one Belarussian. The distribution of alleles for DRPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…The frequency of the 31 allele in our study is within the range found in other Caucasian populations (7.8-15.7%) (Ranum et al, 1994;Watkins et al, 1995;Limprasert et al, 1997;Popova et al, 2001) and is also comparable with the frequency of 11.3% in the Yugoslavian control group (Savic et al, 2001). Comparing different ethnic populations, the 31 allele frequency spans an even broader range (4-20%) (Watkins et al, 1995;Limprasert et al, 1997).…”
Section: Resultssupporting
confidence: 86%
“…The frequency of the 31 allele in our study is within the range found in other Caucasian populations (7.8-15.7%) (Ranum et al, 1994;Watkins et al, 1995;Limprasert et al, 1997;Popova et al, 2001) and is also comparable with the frequency of 11.3% in the Yugoslavian control group (Savic et al, 2001). Comparing different ethnic populations, the 31 allele frequency spans an even broader range (4-20%) (Watkins et al, 1995;Limprasert et al, 1997).…”
Section: Resultssupporting
confidence: 86%
“…However, there were significant differences for the Kalmyk and Yakut populations of Asian origin, as well as for Uralic Komis, Mari, and Bashkirs. The differences observed are similar to those obtained based on other DNA polymorphisms (Belyaeva et al, 1999(Belyaeva et al, , 2003Bermisheva et al, 2001;Khar'kov et al, 2004;Kravchenko et al, 2002;Malyarchuk et al, 2001Malyarchuk et al, , 2002Mirabal et al, 2009;Orekhov et al, 1999;Popova et al, 1999Popova et al, , 2001Shabrova et al, 2004) and are in good agreement with ethnohistorical (Ageeva, 2000) and anthropological data (Alexeeva, 1973, Sedov, 1979. These observations underscore the significance of the 3APOB minisatellite locus for population genetics research.…”
Section: The 3apob Minisatellite Polymorphism In Human Population Resupporting
confidence: 79%
“…The Eastern Slavonic linguistic group (Indo-European linguistic family) was represented by samples from Russian populations from the European (northwestern) part of Russia (Oschevensk, Belaia Sluda, Kholmogory, Mezen, Kursk, Novgorod, Cossacks, Sychevka, Kostroma, and Smolensk), and six Byelorussian populations (Grodno, Pinsk, Mjadel, Bobruisk, Nesvij, and Khoiniki) from different regions of the Republic of Belarus (for a detailed description of the Byelorussians, see Popova et al (Popova et al, 2001). The Belaia Sluda group is an isolated Russian population living at the border of the Arkhangelsk region of northern Russia with the Republic of Komi.…”
Section: The 3apob Minisatellite Polymorphism In Human Population Rementioning
confidence: 99%
“…According to ALFRED Detailed Record information (http://alfred.med.yale.edu/alfred/recordinfo.asp), the Adygei, an ethnic group of the Russian Caucasus, can be traced back to at least the 6th century. Since they were conquered by the Russian Empire in the 19th century, much of the Adygei population was forced to immigrate to Turkey and other Middle Eastern countries (Chang et al, 1996;Popova et al, 2001). Of the original 1.2 million individuals, approximately 800,000 survived the exodus.…”
Section: Discussionmentioning
confidence: 99%